Nutrition knowledge, cooking practices, and consumption of indigenous leafy vegetables among households in Sagnarigu Municipality, Ghana (Ghana Journal of Science, Technology and Development, 2022)
This study assessed nutrition knowledge, cooking practices, and consumption of indigenous leafy vegetables (IGLVs) among households in the Sagnarigu Municipality, Ghana. A structured questionnaire was employed to collect data on socio-demographics, nutrition knowledge scores, cooking practices, and consumption of IGLVs in the Sagnarigu Municipality. The study was cross-sectional, with a multi-stage sampling to select 399 respondents responsible for preparing family meals. More than half of the respondents had a low nutrition knowledge of IGLVs. Respondents with basic education were 67% (OR = 0.410, 95% CI: 0.170–0.986, p = 0.047) less likely to have high nutrition knowledge of IGLVs than those with tertiary education. Most respondents (65.7%) chopped their IGLVs before washing, and almost all (90.2%) discarded stock after cooking. Concerning the consumption of IGLVs, almost all respondents’ households consumed kenaf and jute leaves representing 90.2% and 99.5% respectively. A few of the respondents indicated that availability, low cost and high nutrient content were significant drivers in the consumption of IGLVs (27.1%, 13.3% and 8.8%, respectively). Therefore, interventions by both the government and non-governmental organisations to increase nutrition knowledge and consumption of IGLVs should include strategies to promote the production, utilisation, and commercialisation of IGLVs, especially in the Northern Region.